The Teachers Readiness Of Integrative Thematic Learning in Elementary School (Exploration Study at Elementary School Teacher of Surakarta Academic Year 2017/2018) - Oktiana Handini (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The Research purpose was to determine The Teachers Readiness OfIntegrative Thematic Learning in Elementary School (Exploration Study atElementary School Teacher of Surakarta Academic Year 2017/2018). Theresearch method used survey technique of quantitative research. Thepopulation were 80 Elementary School teachers in the ninth cluster and thesampling technique was purposive random sampling., consistst of TempelElementary School, Banyuanyar 2 Elementary School, Sumber 5Elementary School, Alfalah Elementary School and Fokus ElementarySchool.The data collection was questionnaire that to know the TeachersReadiness Of Integrative Thematic Learning. The questionnaire of TeachersReadiness Of Integrative Thematic Learning were dimensions, e.icurriculum concept understanding, teacher responsesiveness, responsibility,teacher self oriented, teacher perspective and teacher self confidence.Theresult revwal that The Teachers Readiness Of Integrative ThematicLearning in Elementary School only slightly more than general, findingindicates that curriculum concept understanding needed intensive trainningin order to improve effectively learning process in classroom.Keyword: The Teachers Readiness, Integrative Thematic Learning